PERAN ORANG TUA DAN VARIASI MAKANAN DALAM MENINGKATKAN NAFSU MAKAN ANAK USIA PRASEKOLAH - Rizkiyah, Sarifatur; Astutik Andayani, Sri; Fatkhur Rahman, Handono (Jurnal Keperawatan dan Kesehatan, 2026)
Background: Low appetite in preschool-aged children is a common nutritional problem that may affect children’s growth and development. Inadequate appetite can lead to insufficient nutritional intake and increase the risk of malnutrition. Parental roles and food variety are considered important factors influencing children’s eating behavior and appetite. Objective: This study aimed to determine the relationship between parental role and food variety with appetite among preschool-aged children. Methods: This study used a quantitative approach with a cross-sectional design. The sample consisted of 116 parents of preschool-aged children selected using a total sampling technique. Data were collected using questionnaires assessing parental role, food variety, and children’s appetite. Data analysis was conducted using the Spearman Rank test. Results: The findings showed a significant relationship between parental role and children’s appetite (p-value < 0.05), as well as between food variety and children’s appetite (p-value < 0.05). Better parental involvement and more varied food presentation were associated with higher appetite levels in children. Conclusion: Parental role and food variety are significantly associated with appetite in preschool-aged children. Active parental involvement and attractive, varied food presentation can help improve children’s appetite and support optimal nutritional status.